ANALISIS PERILAKU BANGUNAN TOWER ATC MENGGUNAKAN SISTEM SHEAR WALL DAN TANPA SHEAR WALL (STUDI KASUS: TOWER ATC PADA BANDAR UDARA INTERNASIONAL SULTAN AJI MUHAMMAD SULAIMAN, SEPINGGAN, BALIKPAPAN) Author(s) Gerry Rahadiansyah, Niken Warastuti, Fadli Kurni - Gerry Rahadiansyah; Niken Warastuti; Fadli Kurnia (Jurnal Infrastruktur, 2018)
Needs for air transportation cause traffic congestion in air generally perceived as consumers / passenger service users .Often there was an accident in flight , offense an airspace conducted by aircraft that makes passengers not safe. Therefore, it requires a watchtower air traffic or Air Traffic Control (ATC). On ATC Tower case which is a 9 stories building, the lateral retaining structural systems that can be used are shear wall system and without shear wall system. The analysis was performed to get structure behavior differences between two building models and better lateral retaining system for ATC Tower based on its structural behavior. The values of the analysis results shown that the two models are equally good and acceptable based on its torque, shear force, period of vibration, story drift and displacement. However, for ATC Tower case, the structural behavior is better when using shear wall or on 1st modeling because of its smaller moment, shear forces, and displacement.